2014
DOI: 10.1016/j.antiviral.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-influenza virus activity of 4-oxo- or thioxo-4,5-dihydrofuro[3,4-c]pyridin-3(1H)-ones

Abstract: A target-free approach was applied to discover anti-influenza viral compounds, where influenza infected Madin-Darby canine kidney cells were treated 7500 different small organic chemicals individually and reduction of virus-induced cytopathic effect was measured. One of the hit compounds was (Z)-1-((5-fluoro-1H-indol-3-yl)methylene)-6-methyl-4-thioxo-4,5-dihydrofuro[3,4-c]pyridin-3(1H)-one (15a) with half-maximal effective concentrations of 17.4-21.1μM against influenza A/H1N1, A/H3N2 and B viruses without any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Here, the 4-h incubation of influenza A virus PR8 was optimized for nuclear localization of NP. The result clearly showed that both PC5 and PC7 inhibit the early steps similar to EGCG, which is a virus entry blocker [ 20 ]. As expected, PC8 did not affect NP signal intensity or its localization within 4 h after virus infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the 4-h incubation of influenza A virus PR8 was optimized for nuclear localization of NP. The result clearly showed that both PC5 and PC7 inhibit the early steps similar to EGCG, which is a virus entry blocker [ 20 ]. As expected, PC8 did not affect NP signal intensity or its localization within 4 h after virus infection.…”
Section: Resultsmentioning
confidence: 99%
“…Cell viability was measured according to our previous report [ 20 ]. In brief, MDCK cells were seeded in 96-well plates and grown until 100% confluence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were then incubated with 50 µl of 2-fold diluted P0 supernatants for 1 h. After removing unabsorbed virus, the cells were incubated at 35°C for 2 or 3 days. Cell viability was measured using a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromide assay (MTT; Sigma Aldrich) as described previously[ 32 ]. For plaque assay, confluently grown MDCK cells in 48-well plates were infected with 100 µl of 10-fold serially diluted viruses at 35°C for 1 h. After washing with PBS, cells were grown in FBS-free MEM with 2 µg/ml TPCK-trypsin and 0.6% CMC (Sigma Aldrich) for 3 days[ 25 ].…”
Section: In Vitro Dinucleotide Synthesis and Papg Extension Assaysmentioning
confidence: 99%
“…Each mutation site is highlighted in a box. Synthetic promoters were subjected to the RdRp reaction as templates in the presence of ATP and [α-32 P]GTP (ppp*G). vUA(S) or cUA(s) without RdRp [(-)RdRp] was loaded as a negative control.…”
mentioning
confidence: 99%